FACTORS AFFECTING CSR DISCLOSURE - Hendrata, Fiorensa Jasmine; Suhendah, Rousilita (International Journal of Application on Economics and Business, 2024)
This study aims to determine the effect of the influence of board size, firm size, leverage, and audit size on Corporate Social Responsibility Disclosure (CSRD) in the Consumer Non-Cyclicals sector listed on the IDX in 2019-2021. The sample was selected using criteria, namely Consumer Non-Cyclicals sector companies listed on the IDX, publishing annual reports, using IDR currency in their reporting, and presenting complete information in accordance with research needs. The criteria resulted in 68 companies as samples processed with the e-Views 12 and Microsoft excel. Factors that are expected to affect CSR disclosure as well as being independent variables are board size, firm size, leverage, and audit size variables. The results showed significant results from firm size variables, except for size, leverage, and audit size variables. However, the results of this study lack the ability to describe the overall situation and the period studied is limited. So future researchers can expand the scope of research using other sectors such as the Consumer Cyclicals, Industrials, or Technology sector and extend the research period up to 5 years.